AN ECO - FRIENDLY APPROACHFORTHE MANAGEMENTOF NEMATODES ASSOCIATED WITH CHILLI (Biological Sciences - PJSIR, 2004)
This investigation focuses on the effects of three organic amendments namely Fertinemakil and sugarcane bagasse alone or in combination on the population density of three nematode species and yield of chilli. For the purpose of comparison, a chemical nematicide carbofuran was also used. Population densities of Helicotylenchus indicus, Tylenchorhynchus curvus and Meloidogyne spp. (J2) were markedly reduced by the treatments. Yield of chilli was increased significantly over the control by all treatments except sugarcane bagasse alone. However, highest yield was obtained in carbofuran treatment.